SIFAT TOKSISITAS DARI EKSTRAK KASAR BATANG MERUNG (Coptosapelta tomentosa (Blume) Valenton ex K. Heyne) BERDASARKAN NILAI LC50 - Emakana Lestari Br Kaban; Daniel Daniel; Saibun Sitorus (PROSIDING SEMINAR KIMIA, 2019)
Research on phytochemical tests and toxicity of the merung stem merung (Coptosapelta tomentosa (Blume) Valenton ex K. Heyne) has been carried out. Extraction from the stem of the merung was carried out using solvents namely methanol. The results of the phytochemical test on crude extracts of the stem of the merung stem contains phenolic compounds, steroids and flavonoids. Based on the results of toxicity tests on shrimp larvae (Artemia salina Leach) showed in crude extracts had LC50 values of 383.6 ppm. Keywords: Merung Stem, Phytochemical Test, Toxicity.